Перспективи розвитку подієвого туризму в Україні (на прикладі Харківської області) - Бакманян, Ані Каренівна; Bakmanyan, A. K. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Роботу присвячено дослідженню перспектив розвитку подієвого туризму в Україні на прикладі Харківської області. Досліджено сутність поняття та основні чинників розвитку подієвого туризму. Розглянуто класифікацію подієвого туризму. Вивчено зарубіжний досвід реалізації проєктів подієвого туризму. Охарактеризовано ресурсний потенціал розвитку подієвого туризму в регіоні. Проаналізовано регіональні особливості розвитку подієвого туризму. У підсумку сформульовано практичні рекомендації розвитку подієвого туризму з урахуванням безпекового контексту, локальних ініціатив та міжнародної підтримки.

This paper is devoted to the prospects for the development of event tourism in Ukraine, with a specific focus on the Kharkiv region. It defines the concept of event tourism and identifies the key factors influencing its formation and transformation. A classification of event tourism formats is proposed, and international best practices in the implementation of event tourism projects are analyzed. Particular attention is paid to the resource potential of the Kharkiv region, including its cultural infrastructure, institutional capacity, and community engagement. The study provides a detailed assessment of the current state and regional characteristics of event tourism in Kharkiv during the period of 2021–2024. Based on the findings, practical recommendations are formulated for the post-crisis recovery and strategic development of the sector, taking into account safety conditions, local initiatives, and international support mechanisms.
Prospects for the development of event tourism in Ukraine (case study of Kharkiv region)
Керівник: Панова Ірина Олексіївна, кандидат економічних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES; подієвий туризм; туристична інфраструктура; Харківська область; культурна подія; туристичний потенціал; регіональний розвиток; event tourism; tourism infrastructure; Kharkiv region; cultural event; tourism potential; regional development